Microplastics on the growth of plants and seed germination in aquatic and terrestrial ecosystems - Y.S.K. De Silva; U.M. Rajagopalan; H. Kadono (Global Journal of Environmental Science and Management)
Growth of plants, apart from being complex and highly dynamic, is directly dependent on the environmental conditions, particularly the quality of soil for terrestrial plants and the water quality for aquatic plants. Presence of microplastics in the environment may affect the plant growth in numerous ways depending on the contents of the growing medium. However, increasing presence of microplastics at an alarming rate due to its pervasive usage and mismanagement of plastics have led to significant environmental problems. Several research studies have been conducted as well as reviewed to investigate the toxic effects of microplastics on aquatic systems, but studies that investigate the toxic effect of microplastics on the terrestrial systems are limited. Hence, in this review the individual and the combined effects of microplastics on the growth of plants and seed germination in both aquatic and terrestrial ecosystems are concisely discussed. At the beginning accumulation of microplastics on aquatic and terrestrial ecosystem is discussed and the reasonable solutions are highlighted that can mitigate the effects from the widespread increase of the plastic debris. Thereafter, the individual and combined effect of microplastics on seed germination and plant growth is reviewed separately while summarizing the important aspects and future perspectives. This review will provide an insight into the existing gap in the current research works and thus could offer possible implications on the effect of microplastics on plant growth and seed germination in aquatic and terrestrial ecosystem.   ==========================================================================================COPYRIGHTS©2021 The author(s). This is an open access article distributed under the terms of the Creative Commons Attribution (CC BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, as long as the original authors and source are cited. No permission is required from the authors or the publishers.==========================================================================================